2019
DOI: 10.1002/jso.25507
|View full text |Cite
|
Sign up to set email alerts
|

Identifying subgroups of well‐being among patients with cancer: Differences in attitudes and preferences around surveillance after curative‐intent surgery

Abstract: Background Patient perceptions and preferences related to postoperative surveillance are not yet well defined. Methods A cross‐sectional analysis of the surveillance practice preferences and attitudes was undertaken based on subgroups derived from clustering participants for measures of well‐being, including financial toxicity, emotional, family/social, and functional well‐being. Results Among 212 participants, the average age was 58.1 years and most patients were female (57.1%) and white (90.2%). Common malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…On the other hand, surveillance scans could also lead to relief in cases in which no recurrence of disease is found. 48 It is unlikely that patients would be willing to accept a no-surveillance strategy, but whether patients are willing to wait 1 y for a first scan is unclear. As such, more research and patient involvement are needed to include this aspect into cost-effectiveness analyses.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, surveillance scans could also lead to relief in cases in which no recurrence of disease is found. 48 It is unlikely that patients would be willing to accept a no-surveillance strategy, but whether patients are willing to wait 1 y for a first scan is unclear. As such, more research and patient involvement are needed to include this aspect into cost-effectiveness analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Interoperability and care coordination include the trustworthy exchange of patient information across various healthcare practitioners and systems. In order to provide efficient care coordination and informed decision-making, it is essential for authorized individuals to have confidence in the precision and confidentiality of the data that is being shared [33]. The use of BT enables healthcare professionals to securely and efficiently exchange data, fostering trust by enabling the seamless sharing of patient information while maintaining privacy and data integrity.…”
Section: Trust Theorymentioning
confidence: 99%
“…Psychological well-being is defined as managing responses to existential challenges in life (such as pursuing meaningful goals, and establishing relationships with others) (16). Kelly et al (17) reported that patients with low well-being reported higher feelings of tension, anxiety, and insecurity. It's known that in order to manage the long-term effect of cancer treatment, well-being of people living with disease should be supported as well as the surveillance and treatment of the disease (18).…”
mentioning
confidence: 99%